2004
DOI: 10.1126/science.1095140
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Ordered, Robust, Three-Dimensional Gold Nanocrystal/Silica Arrays

Abstract: We report the synthesis of a new nanocrystal (NC) mesophase through self-assembly of water-soluble NC micelles with soluble silica. The mesophase comprises gold nanocrystals arranged within a silica matrix in a face-centered cubic lattice with cell dimensions that are adjustable through control of the nanocrystal diameter and/or the alkane chain lengths of the primary alkanethiol stabilizing ligands or the surrounding secondary surfactants. Under kinetically controlled silica polymerization conditions, evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
422
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(431 citation statements)
references
References 24 publications
6
422
1
2
Order By: Relevance
“…In the simplest and more extensive applied methodology, previously synthesized gold cores stabilized by surfactants or polymers are coated with silica using one of abovementioned procedures. However, one-step approaches based on (W/O) microemulsions, where both the synthesis of the cores and the silanization process take place in-situ have been successfully employed using a wide variety of surfactants, such as Igepal CO-520 [poly(5)oxyethylene-4-nonylphenyl-ether] [173] or CTAB [174] . It is worth noting that the choice of surfactant is a highly relevant factor in the design of a microemulsion, because it determines the size of the emulsion droplets, which in turn has an infl uence on the homogeneity and the thickness of the coating.…”
Section: Dielectric Coatingsmentioning
confidence: 99%
“…In the simplest and more extensive applied methodology, previously synthesized gold cores stabilized by surfactants or polymers are coated with silica using one of abovementioned procedures. However, one-step approaches based on (W/O) microemulsions, where both the synthesis of the cores and the silanization process take place in-situ have been successfully employed using a wide variety of surfactants, such as Igepal CO-520 [poly(5)oxyethylene-4-nonylphenyl-ether] [173] or CTAB [174] . It is worth noting that the choice of surfactant is a highly relevant factor in the design of a microemulsion, because it determines the size of the emulsion droplets, which in turn has an infl uence on the homogeneity and the thickness of the coating.…”
Section: Dielectric Coatingsmentioning
confidence: 99%
“…While previous approaches for metal aerogels were based on the modification of oxide-based aerogels with metal nanoparticles for obtaining highly catalytically active materials (Pajonk 1997;Hüsing & Schubert 1998;Campbell 2004;Jiang & Gao 2006;Vallribera & Molins 2008), with this approach the resulting highly porous macroscopic monoliths are completely non-supportedly built only from metal nanoparticles. Owing to their large surface and the lack of supporting material, these monoliths have an enormous advantage in comparison with previously reported superstructural materials from metal nanoparticles such as mesoporous platinum-carbon composites (Warren et al 2008), gold nanoparticles interlinked with dithiols (Joseph et al 2009), nanochains of hybrid palladium-lipid nanospheres as reported by Zhou et al (2009), electrocatalytically active nanoporous platinum aggregates as reported by Viswanath et al (2009), foams (Banhart 2001;Schroers et al 2003) and highly ordered two-dimensional and three-dimensional supercrystals (Kiely et al 1998;Rabani et al 2003;Fan et al 2004;Kalsin et al 2006;Shevchenko et al 2006), artificial opals (Lu et al 2005a,b), fungal templated (Bigall et al 2008a) or even non-supported assemblies of dithiol-cross-linked supraspheres (Klajn et al 2007(Klajn et al , 2008. The averaged densities of the novel metal nanoparticle hydro-and aerogels were determined to be 0.016 g cm −3 corresponding to approximately 1/1000th of the averaged bulk density of gold and silver, which is two orders of magnitude lower than that of the reported foams.…”
Section: Hydrogels and Aerogels From Noble Metal Nanoparticlesmentioning
confidence: 99%
“…Perfectly duplicating topology of the hard template derives the replica. In particularly, the Au-silica mesostructured superlattice thin film is a model of the hard-template approach which is templated by gold nanoparticles (87). Frequently used inorganic hard templates are anode porous alumina (88), mesoporous silica (75), etc.…”
Section: Confined-space Assemblymentioning
confidence: 99%